The Effect of Volcano Ash and Goat Manure on The Growth of Robusta Coffee (Coffea canephora) Seedlings - Wivo Tiara Novio; Adrinal; Zahlul Ikhsan (Jurusan Budidaya Perkebunan, 2026)
Increasing the production of robusta coffee plants (Coffea canephora) can begin with selecting quality seeds. Improving seed quality can be done through fertilization using ameliorants and organic materials. Volcanic ash and goat manure are ameliorants and organic materials used in improving the planting medium. This study used a completely randomized design (CRD) with two factors: volcanic ash (25, 50, 75 g/polybag) and goat manure (15, 30, 45 g/polybag). The results of this study showed an interaction between volcanic ash and goat manure on the growth in height, shoot dry weight, and the root crown ratio of robusta coffee seedlings. The application of volcanic ash affects plant height, stem diameter, and the root crown ratio of robusta coffee seedlings. The application of goat manure affected plant height, leaf number, and the root-to-shoot ratio of Robusta coffee seedlings. The best ratio was 50 g volcanic ash per polybag and 45 g goat manure per polybag, which optimally increased the growth of Robusta coffee seedlings compared to other treatments. These results indicate that using volcanic ash with goat manure can be an effective alternative organic fertilizer to support coffee seedling growth and improve the fertility of the growing medium.